2015
DOI: 10.1589/jpts.27.1113
|View full text |Cite
|
Sign up to set email alerts
|

Does proprioceptive system stimulation improve sit-to-walk performance in healthy young adults?

Abstract: [Purpose] Sit-to-walk performance is linked to proper proprioceptive information processing. Therefore, it is believed that an increase of proprioceptive inflow (using muscle vibration) might improve sit-to-walk performance. However, before testing muscle vibration effects on a frail population, assessment of its effects on healthy young people is necessary. Thus, the aim of this study was to investigate the effects of muscle vibration on sit-to-walk performance in healthy young adults. [Subjects and Methods] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…This issue remains controversial. For example, Pereira and colleagues demonstrated that local muscle vibration does not improve the sit-to-walk performance of healthy young adults 26 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This issue remains controversial. For example, Pereira and colleagues demonstrated that local muscle vibration does not improve the sit-to-walk performance of healthy young adults 26 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, since gait initiation performance is highly based on postural responses executed before the first step [8], we expected a frequency manipulation effect. We suggest that vibration frequency manipulation effects are restricted to upright stance and were suppressed by superior volitional commands during the step execution [9,19]. Voss et al [30] findings support this hypothesis -the authors found that pre-programmed movement setting interrupts the somatosensory influx to the central neural system.…”
Section: Discussionmentioning
confidence: 61%
“…In the Be condition, since vibration effects are discontinued as soon as the vibration is interrupted [18] and the participants took another ~0.37 seconds to perform the first APA phase, the vibration effects would already have disappeared at the WT onset. In the same way, in the Du condition, vibration effects were suppressed by volitional movement execution [9,19]. Therefore, this lack of significant results was already expected.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“… 5 Finally, the RCVibro System was used to demonstrate the role of proprioception on the performance of sit-to-walk in healthy young individuals. 27 …”
Section: Discussionmentioning
confidence: 99%